2021
DOI: 10.3390/min11101107
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Curing under Applied Stress on the Mechanical Performance of Cement Paste Backfill

Abstract: After placing the Cement Paste Backfill (CPB) slurry in mined cavities underground, during the setting and hardening processes, the weight and hydrostatic pressure of the upper-layer CPB slurry applies an axial load over the bottom-layer CPB materials, which is called the self-consolidation of CPB slurry. Due to this phenomenon, the mechanical properties of in situ CPB could be considerably different from laboratory results. Hence, it is crucial to understand the effect of self-consolidation behaviour on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In the laboratory tests, sand with a grain size of up to 2 mm was used, which is used in cemented paste backfill technologies [24]. Despite the fact that the cement addition usually has not exceeded a few percent [25], with cemented paste backfill technologies, tests have been performed with the cement content exceeding 10% [26]. The highest compressive strength for cylindrical samples consisting of sand, water, and 5%, 10%, and 15% cement volume additions was obtained after four weeks from the time of preparation.…”
Section: Discussionmentioning
confidence: 99%
“…In the laboratory tests, sand with a grain size of up to 2 mm was used, which is used in cemented paste backfill technologies [24]. Despite the fact that the cement addition usually has not exceeded a few percent [25], with cemented paste backfill technologies, tests have been performed with the cement content exceeding 10% [26]. The highest compressive strength for cylindrical samples consisting of sand, water, and 5%, 10%, and 15% cement volume additions was obtained after four weeks from the time of preparation.…”
Section: Discussionmentioning
confidence: 99%
“…The input material properties used for the model is adapted from Guo et al, 45 , Qi, et al 46 , and Zhao, et al 47 , as shown in Tables 2 and 3 .…”
Section: Methodsmentioning
confidence: 99%
“…As a result, a considerable amount of fruitful research has been conducted. These studies can be categorized into three main research methods: basic experimental methods [15][16][17], theoretical analysis methods, and numerical simulation methods [18,19]. Fall et al [20][21][22] studied the mechanical characteristics of CPB at curing temperatures of 2, 20, 35, and 50 • C. They found that the curing temperature significantly impacts the mechanical performance of the CPB.…”
Section: Introductionmentioning
confidence: 99%